Застосування мультиплексних каналів передачі інформації у функціонально-стійкому бортовому інформаційно-управляючому комплексі перспективного літального апарату - Машков, О.А.; Вітко, С.Г. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The structure of board informative control complex is developed with consideration of system functional stability requirements. Multiplex channels of data transferring are used to achieve an optimal structure of connections between different modules and subsystems that are integrated in a single board informative control complex.